2020
DOI: 10.1016/j.foodqual.2019.103789
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of temporal dominance of sensations performed by modality (M-TDS) to the sensory perception of texture and flavor in semi-solid products: A case study on fat-free strawberry yogurts

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
(46 reference statements)
2
16
0
Order By: Relevance
“…For example, perceived fattiness became more dominant over the course of consumption, while other attributes (except astringency) became less dominant, perhaps because repeated tasting led to sensory adaptation. Previous research using multi-intake TDS profiling found that attributes related to texture and sapidity gradually increased over time but that there was no intake effect on how long aroma attributes remained dominant [34,[36][37][38]78,79]. However, in these studies, panelists evaluated multiple spoonfuls of product in a row.…”
Section: The Importance Of Employing a Combination Of Sensory Profilimentioning
confidence: 97%
See 2 more Smart Citations
“…For example, perceived fattiness became more dominant over the course of consumption, while other attributes (except astringency) became less dominant, perhaps because repeated tasting led to sensory adaptation. Previous research using multi-intake TDS profiling found that attributes related to texture and sapidity gradually increased over time but that there was no intake effect on how long aroma attributes remained dominant [34,[36][37][38]78,79]. However, in these studies, panelists evaluated multiple spoonfuls of product in a row.…”
Section: The Importance Of Employing a Combination Of Sensory Profilimentioning
confidence: 97%
“…Conventionally, in TDS profiling, different attribute families (taste, texture, and aroma) can be evaluated during different parts of a study ( [37]). Here, however, the choice was made to evaluate the different attribute families at once.…”
Section: The Importance Of Employing a Combination Of Sensory Profilimentioning
confidence: 99%
See 1 more Smart Citation
“…This color change is also influenced by changes in the physiology and chemistry of strawberries. The color change of strawberries is the process of synthesizing carotenoid pigments and flavonoids (Lesme et al, 2020).…”
Section: Color Analysismentioning
confidence: 99%
“…TDS by modality (TDS-M) might help to overcome this problem, as it allows an assessor to select one dominant taste and one dominant texture attribute. This TDS-M method has been proven useful to characterize simultaneous dynamic taste and texture profiles using trained panels (Lesme et al, 2020;Nguyen et al, 2018), but warrants further investigation with consumer panels.…”
mentioning
confidence: 99%